Is fat‐free mass‐based gentamicin dosing regimen preferable than whole‐body weight in neonates? - Kannan Sridharan; Muna Al Jufairi; Eman Al Ansari; Lulwa Alsadah; Howra Wasel (Wiley, 2023)
ABSTRACT Importance Body fluid dynamics and renal maturation status vary during the neonatal period. We hypothesized that differences in peak and trough gentamicin concentrations could be expected. Objective To predict the peak and trough gentamicin concentrations in critically ill neonates and to predict the changes in the predicted peak plasma concentrations of gentamicin following fat‐free mass dosing. Methods Critically ill neonates that received gentamicin and have gentamicin concentration measured were recruited. Fat mass was estimated using skinfold thicknesses. Changes in the peak plasma concentrations (Cmax) using whole‐body weight (estimated using the current dosing regimen) and predicted concentrations following the fat‐free mass‐based dosing were the outcome measures. Results Eighty‐nine critically ill neonates were recruited. Sub‐therapeutic Cmax was estimated using the current dosing regimen in 32.6%, and 22.5% neonates following the first and second doses of gentamicin. Preterm neonates had significantly higher fat mass compared to term neonates. All except one had Cmax above 12 μg/ml after the first dose and all had after the second gentamicin dose following the predicted fat‐free mass‐based gentamicin dosing. The recommended doses are as follows: extreme preterm: 7.95 mg/kg every 48 h; very preterm: 7.30 mg/kg every 36-48 h; late preterm: 5.90 mg/kg every 36-48 h; and term neonates at 5.10 mg/kg every 24 h. Interpretation Fat‐free mass dosing may be considered for obtaining optimal therapeutic effects in the neonatal population.